Management of ticlopidine associated pancytopenia - (:unkn) unknown (My University, 1999)
Koroner arter stent uygulaması yapılan bir hastada tiklopidine bağlı gelişen pansitopeni olgusu sunulumaktadır. Hasta antibiyotik ve granülosit koloni uyarıcı faktör tedavisine (G-CSF) yanıt vermiştir. Seyrek görülen bu komplikasyonun tedavisi ile ilgili literatür incelenmiştir .

A case of pancytopenia secondary to ticlopidine in a patient undergoing coronary artery stenting responded to granulocyte colony stimulating factor (G-CSF) and antibiotic therapy following cessation of the drug. The case is described and recent literature on this rare manifestation is reviewed.
Keywords: Onkoloji